Elephant corridor use and threats in the eastern range of Amboseli elephants, Kenya - John Kioko; Simon Seno (Pachyderm)
Elephant corridors are critical in safeguarding wildlife dispersal areas. Understanding the level of corridor use by elephants and the threats they face is important for prioritizing their conservation. Following cessation of heavy elephant poaching in 1970s and 1980s in the Amboseli area, elephants associated with Amboseli National Park (NP) began to reoccupy their eastern range. However, emerging changes in land use and ownership may be hindering elephant movements and range utilization. The status of three corridors and their use by elephants and other wildlife in the eastern range of Amboseli elephants was assessed. The intensity of daily corridor use by elephants differed among three corridors that were observed in this study. There was a strong relation ship between elephant and other wildlife use of the corridors. Elephant corridors were significantly threatened due to constriction by human settlement, agriculture, land subdivision and existence of non-negotiated land tenure. Primarily, these threats have been occasioned by individualization of land. Potential solutions to preserve critical elephant corridors include the initiation of community-based conservation programmes such as conservancies and land lease agreements.